The Impact of Full-Scale Simulation Training Based on Kolb's Learning Cycle on Medical Prehospital Emergency Teams: A Multilevel Assessment Study. Issue 5 (October 2020) - Secheresse, Thierry; Pansu, Pascal; Lima, Laurent
Abstract : Introduction: Using simulation to train teams in out-of-hospital cardiac arrest management is recommended to improve team effectiveness. The aim of this study was to assess the impact of a specific cardiac arrest management simulation training program inspired by the principles of Kolb's learning cycle. Method: All the staff in a medical prehospital emergency unit participated in this program. Both individual and team levels were evaluated: on an individual level, we assessed attitudes toward training and medical knowledge of cardiac arrest management; on a team level, we assessed team behavior during simulated cardiac arrest and learning transfer in clinical practice. Results: In addition to the satisfaction of the participants, the results showed a positive effect on medical knowledge and team behavior and an improvement in the management of patients suffering cardiac arrest. Conclusions: These findings confirm the usefulness of a simulation training program containing the 4 steps of Kolb's cycle for emergency teams. Abstract : Supplemental digital content is available in the text.